2002
DOI: 10.1002/app.10406
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among crystalline morphology of PEEK, interface bond strength, and in‐plane mechanical properties of carbon/PEEK composites

Abstract: ABSTRACT:The effect of the cooling rate on in-plane and interlaminar properties of carbon fiber/semicrystalline PEEK matrix composites was studied. Strengths and moduli were measured in tension, flexure, and interlaminar shear, all of which were shown to correlate, to different degrees, with the fiber-matrix interface adhesion and the bulk matrix properties. The in-plane and interlaminar properties, in general, increased with a decreasing cooling rate, which was attributed to changes in the failure mechanism f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…Although some steps are taken to model the subsequent consolidation process during thermoforming (Xiong et al, 2019), an accurate model of the mesoscopic geometry of the fiber reinforcement at the interface after overmolding (involving deconsolidation as well as the subsequent interaction with the polymer melt) is still beyond current predictive capability. Nevertheless, when analysing the stress state at failure for the rib stiffened V-shape specimens, it was found that the maximum shear stress value is similar to interlaminar shear strengths of various C/PEEK laminates reported by e.g., Jang and Kim (1997), Gao and Kim (2002), and Gupta et al (2002). This suggests that the mechanical performance of overmolded parts may well be suited for (semi) structural applications, provided the process conditions are sufficient to achieve a proper bonding.…”
Section: Healing Approachmentioning
confidence: 53%
“…Although some steps are taken to model the subsequent consolidation process during thermoforming (Xiong et al, 2019), an accurate model of the mesoscopic geometry of the fiber reinforcement at the interface after overmolding (involving deconsolidation as well as the subsequent interaction with the polymer melt) is still beyond current predictive capability. Nevertheless, when analysing the stress state at failure for the rib stiffened V-shape specimens, it was found that the maximum shear stress value is similar to interlaminar shear strengths of various C/PEEK laminates reported by e.g., Jang and Kim (1997), Gao and Kim (2002), and Gupta et al (2002). This suggests that the mechanical performance of overmolded parts may well be suited for (semi) structural applications, provided the process conditions are sufficient to achieve a proper bonding.…”
Section: Healing Approachmentioning
confidence: 53%
“…Composite materials with better properties can be obtained by the combination of PEEK and CF. CF can act as a heterogeneous nucleating agent to promote the crystallization of PEEK in composites [8,9,10]. However, due to the high melting viscosity of PEEK itself and its insolubility in many solvents, the preparation of continuous CF/PEEK composites has always been a scientific problem to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…18 For example, a thick transcrystalline layer increases the stress transfer, probably because of the increased radial compressive stresses. 20,28,29 Thus, the V C 2016 Wiley Periodicals, Inc. knowledge of interfacial structures and mechanical properties together with the influences of the thermal history on them helps in understanding and tailoring the composite properties better. 20 According to the previous reports, a 50-nm-thick transcrystalline layer results in an additional 5% enhancement in the overall composite modulus because the modulus of such crystalline regions is greater than that of the bulk polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] In thermoplastic composites, the aforementioned interfacial characteristics are greatly dominated by variations in the thermal processing histories such as cooling rate. 20,28,29 Thus, the V C 2016 Wiley Periodicals, Inc. knowledge of interfacial structures and mechanical properties together with the influences of the thermal history on them helps in understanding and tailoring the composite properties better.…”
Section: Introductionmentioning
confidence: 99%